Preparation method and application of ruthenium-based nickel-rich material catalyst
By preparing calcium-promoted ruthenium-based nickel-rich catalysts, the problem of low catalyst efficiency in the low-temperature and low-pressure ammonia synthesis process was solved, realizing a highly efficient low-temperature and low-pressure ammonia synthesis reaction, and reducing energy consumption and greenhouse gas emissions.
Patent Information
- Application Number
- CN202410598552.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-11-18
AI Technical Summary
Existing ammonia synthesis processes are energy-intensive, emit greenhouse gases during hydrogen production, and lack efficient catalysts at low temperatures and pressures, leading to increased costs.
Using NCA (LiNi0.8Co0.15Al0.05O2) as a support and calcium fluoride as an auxiliary agent, a calcium-promoted ruthenium-based nickel-rich catalyst was prepared by grinding and used for ammonia synthesis reaction at low temperature and low pressure.
Highly efficient ammonia synthesis catalysis was achieved under low temperature and low pressure, significantly improving the specific surface area of the catalyst and the dispersion of ruthenium, thereby enhancing catalytic activity.
Smart Images

Figure CN120961191A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of catalyst material preparation, and particularly relates to a preparation method and application of a ruthenium-based nickel-rich material catalyst. BACKGROUND
[0002] At present, Haber-Bosch process is generally used in the industry to synthesize ammonia, in which nitrogen and hydrogen are used as raw materials, and the production is carried out through catalytic reaction under high temperature and high pressure (400-600 DEG C, 10-40 MPa). The energy consumption of Haber-Bosch process accounts for 1%-2% of the total global energy consumption, in which the hydrogen production process consumes about 80% of the energy of the whole process, and a large amount of greenhouse gas carbon dioxide is discharged in the preparation process of hydrogen from fossil fuels such as petroleum and natural gas, polluting the environment. Therefore, the development trend of the ammonia synthesis industry is to first change the hydrogen production method, and to use renewable energy such as solar energy, wind energy and water energy to produce hydrogen by electrolysis of water; and then to react hydrogen with nitrogen obtained by air separation device to synthesize ammonia. However, the outlet temperature and pressure of the current water electrolysis hydrogen production system are relatively low, which is not matched with the high temperature and high pressure of the traditional ammonia synthesis process. Therefore, in order to avoid the cost of adding heat exchanger and compressor, the ammonia synthesis industry must develop a high-efficiency ammonia synthesis catalyst under low temperature and low pressure. SUMMARY
[0003] The application aims at the deficiencies of the prior art, and provides a preparation method and application of a ruthenium-based nickel-rich material catalyst. 0.8 Co 0.15 Al 0.05 O2) as a carrier, and fluorite as an additive, a calcium-promoted ruthenium-based nickel-rich material catalyst is prepared by using a grinding method, and under the conditions of 400 DEG C, 0.1 MPa and 36000 mL g -1 h -1 h -1 h -1 .
[0004] In order to achieve the above-mentioned purpose, the application adopts the following technical scheme:
[0005] The first aspect of the application is to provide a preparation method of a ruthenium-based nickel-rich material catalyst, and the steps are as follows:
[0006] Step 1: Place a 0.5–5 wt% ammonium fluoride aqueous solution in an ultrasonic environment, and slowly add a 0.5–5 wt% calcium hydroxide suspension. The molar ratio of ammonium fluoride to calcium hydroxide is 1:0.8–1:1.4. After the reaction is complete, centrifuge to obtain the calcium fluoride solid product, heat and dry to obtain crude calcium fluoride, grind and then calcine at high temperature to obtain nano-sized calcium fluoride. Weigh Al2O3 and LiOH·H2O, mix and grind them (where the atomic ratio of aluminum to lithium is 1:10–1:30), mix evenly, and then add Ni. 0.842 Co 0.158 (OH)2 is mixed and ground (where the atomic ratio of nickel to lithium is 1:1 to 1:1.5), and then the resulting mixture is calcined in a tube furnace to obtain the catalyst support NCA (LiNi). 0.8 Co 0.15 Al 0.05 O2);
[0007] Step 2: Mix and grind the catalyst support NCA obtained in Step 1 with the ruthenium source to make it uniformly mixed, and obtain the first mixed powder. The mass fraction of ruthenium in the catalyst is 2-7 wt%.
[0008] Step 3: Mix and grind the first mixed powder with the nano-sized calcium fluoride obtained in Step 1 to make them evenly mixed, and obtain the second mixed powder, wherein the atomic ratio of ruthenium to calcium is 1:1 to 1:7;
[0009] Step 4: Calcine the second mixed powder under a reducing atmosphere. After reduction, the calcium-promoted ruthenium-based catalyst can be obtained.
[0010] Furthermore, the ruthenium source is selected from one or more of dodecyltriruthenium, ruthenium chloride, and ruthenium acetylacetonate.
[0011] Furthermore, the high-temperature calcination described in step one is carried out in a tubular furnace, with a calcination temperature of 150℃ to 400℃, a heating rate of 1℃ / min to 5℃ / min, and a calcination time of 6h to 18h. More preferably, the calcination temperature is 150℃ to 300℃, and the calcination time is 8h to 12h.
[0012] Further, the calcination atmosphere in the tubular furnace mentioned in step one refers to calcination at 200℃ to 1000℃ for 1h to 8h in pure hydrogen, a nitrogen-hydrogen mixture, or a hydrogen-argon mixture. More preferably, the calcination temperature is 300℃ to 800℃, and the calcination time is 2h to 6h.
[0013] Further, the reducing atmosphere in step four is pure hydrogen, a nitrogen-hydrogen mixture, or a hydrogen-argon mixture, the calcination temperature is 200℃~600℃, and the calcination time is 2h~6h. More preferably, the calcination temperature is 300~400℃, and the calcination time is 2h~4h.
[0014] A second aspect of the present invention is to provide a ruthenium-based nickel-rich catalyst prepared by the above method.
[0015] A third aspect of the invention is the application of the above-described catalyst in the ammonia synthesis reaction. The ammonia synthesis reaction is carried out at a temperature of 400°C and a pressure of 0.1 MPa.
[0016] The beneficial effects of this invention are as follows:
[0017] This invention is the first to apply nickel-rich cathode material to the field of ammonia synthesis catalysis. This material has a mature commercial industry, the preparation of the support is very simple, and it can be purchased and used directly. The use of fluoride salt in ammonia synthesis catalyst significantly increases the specific surface area of the catalyst and enhances the catalyst activity in the form of structural additives. Attached Figure Description
[0018] Figure 1 This is a scanning electron microscope image of nanoscale calcium fluoride obtained in Example 1 of the present invention.
[0019] Figure 2 This is a particle size distribution diagram of the nano-sized calcium fluoride obtained in Example 1 of the present invention.
[0020] Figure 3 The X-ray diffraction patterns are those of the catalysts obtained in Example 1 and Comparative Examples 2 and 3 of the present invention.
[0021] Figure 4 This is a scanning electron microscope image of the catalyst obtained in Example 1 of the present invention.
[0022] Figure 5 The images show transmission electron microscopy (TEM) images and ruthenium particle size distribution diagrams of the catalyst obtained in Example 1 of this invention.
[0023] Figure 6 The catalysts obtained in Example 1 and Comparative Examples 1, 2, and 3 of this invention were subjected to a space velocity of 36000 mL g. -1 h -1 Ammonia synthesis performance under conditions of 400℃ and 0.1MPa.
[0024] Figure 7 This refers to the stability of the catalyst obtained in Example 1 of the present invention within 100 hours.
[0025] Figure 8 The kinetic data are for the catalyst obtained in Example 1 of this invention. Detailed Implementation
[0026] To make the solutions and advantages of the present invention clearer, the present invention and its advantages will be described in detail below with reference to specific embodiments and accompanying drawings, but the embodiments of the present invention are not limited thereto.
[0027] Example 1
[0028] A method for preparing a ruthenium-based nickel-rich catalyst includes the following steps:
[0029] Step 1: Weigh 10 mmol of calcium hydroxide and disperse it in 89 g of water to form dispersion A. Weigh 29 mmol of ammonium fluoride and dissolve it in 107 g of water to form solution B. Place the beaker containing the calcium hydroxide dispersion in an ultrasonic cleaner for ultrasonic irradiation. Then, slowly add the ammonium fluoride aqueous solution to the calcium hydroxide dispersion using a peristaltic pump at a dropping rate of 2.5 ml / min and an ultrasonic power of 400 W. The entire process is ultrasonic, lasting approximately 50 minutes. Centrifuge the resulting suspension at 10,000 rpm for 8 minutes. Collect the solid precipitate obtained by centrifugation, which is the product calcium fluoride. Place the product calcium fluoride in an oven at 90°C for 10 hours to dry it and obtain crude calcium fluoride. Grind the crude calcium fluoride in a mortar for 15 minutes. Pour the ground powder into a ceramic boat and place it in a tube furnace. Calcinate the powder in an Ar atmosphere, raising the temperature to 200°C at 4°C / min and holding for 10 hours before cooling to obtain nano-sized calcium fluoride. Weigh out 0.0866g of Al2O3 and 1.4264g of LiOH·H2O, mix and grind for 30 minutes, then add 3g of Ni. 0.842 Co 0.158 (OH)₂ was ground for another 1 hour to ensure all materials were thoroughly mixed. The resulting mixture was placed in a ceramic boat and then placed in a tube furnace. Under an oxygen atmosphere, the temperature was increased to 750°C at a rate of 5°C / min and calcined for 6 hours. After cooling to room temperature, NCA (LiNi) was obtained. 0.8 Co 0.15 Al 0.05 O2). From Figure 1 It can be seen that the homemade calcium fluoride consists of nano-sized particles. Figure 2 It can be seen that the self-made calcium fluoride has a uniform particle size distribution, with an average particle size of 47 nm.
[0030] Step 2: Weigh 0.4g NCA and 0.104g dodecacarbonyltriruthenium, add them to a mortar and mix thoroughly. Then grind for 25 minutes to ensure uniform mixing.
[0031] Step 3: Weigh out 0.478g of calcium fluoride and add it to the mortar. Mix and continue grinding for 25 minutes to ensure even mixing.
[0032] Step 4: Under a 75% H2 / 25% N2 atmosphere, the sample is heated to 400℃ at a rate of 5℃ / min and held at this temperature for 2h to obtain the catalyst 5Ca-Ru / NCA400.
[0033] The catalyst obtained in Example 1 is designated as 5Ca-Ru / NCA400.
[0034] Figure 3 The X-ray diffraction pattern of the catalyst obtained in Example 1 of this invention shows diffraction peaks for calcium fluoride, calcium oxide, lithium fluoride, and nickel. Figure 4 It can be seen that the catalyst consists of nano-sized particles. From Figure 5 Ruthenium particles can be observed, and there is no obvious sintering of ruthenium after the reaction.
[0035] The ammonia synthesis performance of the catalyst was evaluated in a stainless steel reaction tube (Φ = 8 mm) of a pressurized microreactor (MS-C-2f). For each experiment, 0.1 g of catalyst (20–40 mesh) and 0.4 g of silica sand were weighed, mixed, and then loaded into the tube for testing. During catalyst loading, it was crucial to ensure the catalyst remained within the isothermal zone of the fixed bed. Therefore, a certain amount of silica sand was first loaded into the stainless steel reaction tube, followed by the silica sand-catalyst mixture, and finally, a layer of silica sand was placed on top of the catalyst to prevent it from being blown away by excessive airflow. For performance testing, a 75% H₂ / 25% N₂ mixture was used as the feed gas, with a space velocity of 36000 mL g⁻¹. -1 h -1 The reaction pressure was 0.1 MPa, and the temperature was increased to 400℃ at a rate of 2℃ / min. The catalyst was reduced for 2 hours before the activity test. The ammonia synthesis rate (r) was determined by the following method: the outlet gas was collected using 50 ml of dilute sulfuric acid for 3–10 minutes, the concentration of ammonium ions (C) in the collected liquid was measured by ion chromatography (Metroën Eco IC, Switzerland), and finally r was calculated using formula (2-1).
[0036]
[0037] In the formula:
[0038] r is the rate of ammonia synthesis (mol g⁻¹h⁻¹).
[0039] C represents the concentration of ammonium ions in the collected solution (g / L).
[0040] V is the volume (L) of the dilute sulfuric acid collection solution.
[0041] 18 represents the molar mass (g / mol) of the ammonium ion.
[0042] m represents the mass (g) of the catalyst used.
[0043] t represents the time (h) for collecting the outlet gas.
[0044] Figure 7 The figure shows the stability of the catalyst obtained in Example 1 of the present invention within 100 hours. As can be seen from the figure, the catalyst has excellent thermal stability.Figure 8 The figure shows the kinetic data of the catalyst obtained in Example 1 of the present invention, with the catalyst activation energy and reaction order data provided.
[0045] Comparative Example 1
[0046] The NCA prepared in step two of Example 1 was used as a catalyst without any treatment, and its ammonia synthesis reactivity was tested using the same evaluation method as in Example 1.
[0047] The catalyst obtained in Comparative Example 1 is denoted as NCA400.
[0048] Comparative Example 2
[0049] Prepare Ru / NCA400 catalyst without adding calcium fluoride.
[0050] The specific steps are as follows:
[0051] Weigh 0.2 g of NCA and 0.024 g of dodecacarbonyltriruthenium and add them to a mortar, mix them thoroughly, and then grind for 25 min to ensure uniform mixing. Heat the sample to 400 °C at a rate of 2 °C / min under a 75% H2 / 25% N2 atmosphere and maintain this temperature for 2 h to obtain the catalyst Ru / NCA400.
[0052] The sample was heated to 400℃ at a rate of 2℃ / min under a 75% H2 / 25% N2 atmosphere and held at this temperature for 2h to obtain the catalyst Ru / NCA400.
[0053] The catalyst obtained in Comparative Example 2 is designated Ru / NCA400. The ammonia synthesis reactivity was tested using the same evaluation method as in Example 1.
[0054] Figure 3 The X-ray diffraction pattern of the catalyst obtained in Comparative Example 2 of the present invention is shown in the figure. The diffraction peaks of nickel can be observed from the figure.
[0055] Comparative Example 3
[0056] The specific steps for preparing the 2Ca-Ru / NCA400 catalyst are as follows:
[0057] Weigh 0.4g of NCA and 0.06g of dodecacarbonyltriruthenium and add them to a mortar, mix thoroughly, and then grind for 25 minutes until homogeneous. Next, weigh 0.112g of calcium fluoride and add it to the mortar, mix, and continue grinding for 25 minutes until homogeneous.
[0058] The sample was heated to 400℃ at a rate of 2℃ / min under a 75% H2 / 25% N2 atmosphere and held at this temperature for 2h to obtain the catalyst 2Ca-Ru / NCA400.
[0059] The catalyst obtained in Comparative Example 3 was designated 2Ca-Ru / NCA400. Its ammonia synthesis reactivity was assessed using the same evaluation method as in Example 1.
[0060] Figure 3 The X-ray diffraction pattern of the catalyst obtained in Comparative Example 3 of the present invention is shown in the figure. Diffraction peaks of calcium fluoride, calcium oxide, lithium fluoride, and nickel can be observed from the figure.
[0061] The catalysts prepared in Example 1 and Comparative Examples 1, 2, and 3 were evaluated for activity and tested for reaction kinetics according to the specific application example 1. Their composition, structure, and morphology were also characterized. Figure 6 It can be observed that the addition of calcium fluoride significantly enhances the activity of the catalyst. Figure 5 Statistical analysis revealed that the ruthenium particle size in the catalyst was approximately 2 nm, indicating the presence of numerous B5 sites and that the reaction primarily proceeded via a dissociation mechanism. The specific surface area of the 5Ca-Ru / NCA400 catalyst was 25.4 m². 2 g -1 The specific surface area of the catalyst was increased by 8 times compared to Ru / NCA400, indicating that calcium fluoride significantly increased the specific surface area of the catalyst. Meanwhile, the ruthenium dispersion in 5Ca-Ru / NCA400 was 31.9%, significantly higher than the 7.1% in Ru / NCA400, suggesting that calcium fluoride promoted ruthenium dispersion and acted as a structural aid.
[0062] Based on the disclosure and teachings of the foregoing specification, those skilled in the art can make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments described above, and any obvious improvements, substitutions, or modifications made by those skilled in the art based on the present invention are within the scope of protection of the present invention. Furthermore, although some specific terms are used in this specification, these terms are only for convenience of explanation and do not constitute any limitation on the present invention.
Claims
1. A method for preparing a ruthenium-based nickel-rich catalyst, characterized in that, The steps are as follows: Step 1: Place an aqueous solution of ammonium fluoride (0.5–5 wt%) in an ultrasonic environment, and slowly add a suspension of calcium hydroxide (0.5–5 wt%). The molar ratio of ammonium fluoride to calcium hydroxide is 1:0.8–1:1.
4. After the reaction is complete, centrifuge to obtain the solid product of calcium fluoride. Heat and dry to obtain crude calcium fluoride. Grind and calcine at high temperature to obtain nano-sized calcium fluoride. Weigh Al₂O₃ and LiOH·H₂O, mix and grind them together, wherein the atomic ratio of aluminum to lithium is 1:10–1:
30. After mixing evenly, add Ni. 0.842 Co 0.158 (OH)₂ is mixed and ground, wherein the atomic ratio of nickel to lithium is 1:1 to 1:1.
5. The resulting mixture is then calcined in a tube furnace to obtain the catalyst support NCA (LiNi). 0.8 Co 0.15 Al 0.05 O2); Step 2: Mix and grind the catalyst support NCA obtained in Step 1 with the ruthenium source to obtain the first mixed powder. The mass fraction of ruthenium in the catalyst is 2-7 wt%. Step 3: Mix and grind the first mixed powder with the nano-sized calcium fluoride obtained in Step 1 to obtain the second mixed powder, wherein the atomic ratio of ruthenium to calcium is 1:1 to 1:7; Step 4: Calcine the second mixed powder under a reducing atmosphere to obtain a calcium-promoted ruthenium-based catalyst.
2. The method for preparing the ruthenium-based nickel-rich catalyst according to claim 1, characterized in that, The ruthenium source is selected from one or more of dodecyltriruthenium, ruthenium chloride, and ruthenium acetylacetonate.
3. The method for preparing the ruthenium-based nickel-rich catalyst according to claim 1, characterized in that, The high-temperature calcination described in step one is carried out in a tube furnace at a temperature of 150℃ to 400℃, a heating rate of 1℃ / min to 5℃ / min, and a calcination time of 6h to 18h.
4. The method for preparing the ruthenium-based nickel-rich catalyst according to claim 1, characterized in that, The calcination atmosphere in the tubular furnace mentioned in step one refers to calcination at 200℃~1000℃ for 1h~8h in pure hydrogen, nitrogen-hydrogen mixture, or hydrogen-argon mixture.
5. The method for preparing the ruthenium-based nickel-rich catalyst according to claim 1, characterized in that, The reducing atmosphere described in step four is pure hydrogen, a nitrogen-hydrogen mixture, or a hydrogen-argon mixture, the calcination temperature is 200℃~600℃, and the calcination time is 2h~6h.
6. A ruthenium-based nickel-rich catalyst prepared according to any one of claims 1-5.
7. The application of the catalyst according to claim 6 in the ammonia synthesis reaction.
8. The application according to claim 7, characterized in that, The temperature for the ammonia synthesis reaction is 400℃ and the pressure is 0.1MPa.